Saving Children or Blaming Parents – Lessons from Mandated Parenting Classes - Schaefer, Tali (Columbia Journal of Gender and Law, 2010)
What should family law do about divorcing parents? “Teach them a lesson,” a legislative wave sweeping through the United States has answered. As a result of the legislation, growing numbers of divorcing parents are required to attend “parent education programs,” turning these programs from a fad in family courts into an established and mandatory stop on parents’ path to divorce. This legislation mandates informational classes that focus on the harm children suffer as a consequence of divorce and on behaviors parents should change in order to reduce the damage. This Article is the first to analyze the enactment discussions accompanying the legislation and to explore judges’ extensive role in promoting and securing its passage. It demonstrates that despite its child-oriented goals, the legislation is preoccupied with casting a negative judgment on parents’ decision to separate and with blaming parents for the negative effects of divorce. This Article argues that this preoccupation with blaming parents has resulted in laws that do little to help children and much to belittle the tangible negative implications that divorce holds for parents, especially mothers. Doing so, the legislation downplays the role that legal, social and economic forces play in producing the undesired behaviors that classes currently try to eradicate. Moreover, by laying the full responsibility for possible harm to children of divorce in individual parents’ laps, states have also shirked their responsibility for these children.